Food Security of Farm Households in Indonesia’s Border Area, Sebatik Island - Handoyo Mulyo, jangkung; ., Irham; ., Jumeri; Heru Widodo, Agus; Wirakusuma, Gilang; Perwitasari, Hani (International Journal of Engineering and Technology, 2018)
Food is one of the main parts of Indonesian national interests which can determine national stability and sovereignty. Furthermore, every nation has to ensure that all of its citizens can fulfill their daily diet. Many people living in Indonesia’s border areas face challenges in fulfilling food demand, i.e. accessibility and high cost of farming. This study aimed; (1) to know food security level of farm households, (2) to know determinants of that food security level. This study was conducted in Sebatik Island, North Borneo Province, Indonesia. Purposive sampling was employed to define location of this study, while multi stage simple random sampling was used to define a sample of 81 farmer households who are living and cultivating in Sebatik Island. Data were collected with structured questionnaire. Food security level was identified by combining the amount of food consumption and share of food expenditure as the Johnson and Toole approach. Moreover, Logistic model was employed to define determinants of food security level. The result revealed that only 18.95% of farm households were ‘food secure’. Meanwhile, 24.21% and 21.05% of farm households were categorized as ‘vulnerable’ and ‘food insecure’; respectively. Other 35.79% of farm households were known as ‘questionable’ which were lack of food, but they have the ability to increase food consumption. Other result identified that size of household, consumed calorie, and non-food expenditure determined food security level of those farm households. It was recommended that controlling population growth, increasing access of food, and raising household income may improve food security level of farm households.